Photodynamic Therapy Relieves Colitis and Prevents Colitis-associated Carcinogenesis in Mice. Issue 5 (May 2015) - Reinhard, Aurélie; Bressenot, Aude; Dassonneville, Romain; Loywick, Alexandre; Hot, David; Audebert, Christophe; Marchal, Sophie; Guillemin, François; Chamaillard, Mathias; Peyrin-Biroulet, Laurent; Bezdetnaya, Lina
Abstract : Background: Inflammatory bowel diseases are incurable illnesses of the gastrointestinal tract, which substantially enhance the risk of developing colorectal carcinogenesis. Conventional photodynamic therapy is a clinically approved therapeutic modality used in the treatment of neoplastic diseases. Recent preclinical and clinical studies have shown that photodynamic therapy with low doses of photosensitizer and/or light improves inflammatory conditions, including colitis. This study aims therefore at investigating the therapeutic potential of low-dose photodynamic therapy (LDPDT) with a liposomal formulation of meta-tetra(hydroxyphenyl)chlorin (namely Foslip) in the prevention of colitis-associated cancer in mice. Methods: LDPDT efficacy was evaluated by endoscopic, macroscopic, and histological analysis. Myeloperoxidase levels were quantified by enzyme linked immunosorbent assay and cytokines expression by quantitative RT-PCR analysis. The integrity of the intestinal barrier was evaluated by immunostaining, and bacterial composition of the fecal microbiota was determined by 454 pyrosequencing of V3-V4 region of bacterial 16S rRNA genes. Results: LDPDT reduced intestinal tumor growth by decreasing the expression of a wide range of inflammatory mediators and by lowering neutrophil influx. LDPDT treatment prevents onset of a dysbiotic microbiota in the colitis-associated cancer model. Conclusions: LDPDT with Foslip could be considered as a novel treatment modality to prevent colorectal carcinogenesis in patients with inflammatory bowel disease. Abstract : Article first published online 24 March 2015.Supplemental Digital Content is Available in the Text.